Tradisi Dafek Kakawalmuir dalam Perspektif Hukum Keluarga Islam: Studi Kasus Suku Kur di Maluku - Nur Lili Tatroman; M. Amir Mahmud; A. Rudi Maswanto (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
The practice of providing financial aid to siblings, known as Dafek Kakawalmuir, among the Kur ethnic group in Maluku, Indonesia, embodies strong family solidarity and serves as a key social obligation. Employing a qualitative approach, this study examines the tradition through the lens of Islamic family law, focusing on ethical dimensions, financial burdens, and its alignment with Islamic values amid cultural shifts. Data were gathered via semi-structured interviews with five informants from the Maluku community in Banyuwangi. Key findings reveal that the tradition is driven by long-term benefits for descendants, acts of piety, and spiritual rewards, though respondents exhibit limited understanding of its links to Islamic concepts like ‘urf (local custom) and maqāṣid syarī‘ah (objectives of Sharia). The practice transcends gender boundaries, often delaying personal milestones such as marriage. While fostering unity, it risks tensions like economic strain on married supporters. In conclusion, Dafek Kakawalmuir qualifies as a valid ‘urf under Islamic law if it promotes family cohesion without injustice, but Sharia boundaries require education to balance individual rights and collective duties. Policy implications include family dialogue forums and theoretical advancements in integrating local norms with Islamic jurisprudence in Indonesia.